Elucidating the role of non-covalent interactions in unexpectedly high and selective CO2 uptake and catalytic conversion of porphyrin-based ionic organic polymers. Issue 11 (28th April 2021) - Kostakoğlu, Sinem T.; Chumakov, Yurii; Zorlu, Yunus; Sadak, Ali E.; Denizaltı, Serpil; Gürek, Ayşe G.; Ayhan, Mehmet M.
Abstract : Here, we present viologen-porphyrin based ionic covalent organic polymers (H2-ICOP and Zn-ICOP ) with multiple CO2 -philic sites. Abstract : Here, we present viologen-porphyrin based ionic covalent organic polymers (H2-ICOP and Zn-ICOP ) with multiple CO2 -philic sites. The specific surface areas of H2-ICOP and Zn-ICOP were found to be 9 m 2 g −1 and 20 m 2 g −1, respectively. CO2 uptake analyses reveal that H2-ICOP exhibits very high CO2 capture uptake (62.9 mg g −1 ), which is one of the highest values among previously reported ICOPs. The results indicate very efficient non-covalent interactions between H2-ICOP and CO2 . The possible non-covalent interactions of hydrogen (OCO2 ⋯H–N), tetrel (CCO2 ⋯N, CCO2 ⋯Cl − ), pnicogen (OCO2 ⋯N + ), and spodium bonds (OCO2 ⋯Zn) between CO2 and H2-ICOP and Zn-ICOP are investigated via symmetry adapted perturbation theory (SAPT) analysis and electrostatic potential maps (MEP). The strength of non-covalent interactions in H2-ICOP and Zn-ICOP is decreasing in the following order Δ E C⋯N > Δ E C⋯Cl − > Δ E O⋯N + and Δ E Zn⋯O > Δ E C⋯Cl − > Δ E C⋯N > Δ E O⋯N +, respectively. The major CO2 uptake contribution comes from CCO2 ⋯N tetrel bonding (−22.02 kJ mol −1 ) interactions for H2-ICOP, whereas OCO2 ⋯Zn spodium bonding (−21.065 kJ mol −1 ) interactions for Zn-ICOP . H2-ICOP has more CO2 -philic moieties with powerful non-covalent interactions compared to Zn-ICOP, which is in good agreement with the experimental results. Furthermore, the CO2 catalytic conversion performances of Zn-ICOP and H2-ICOP gave good yields of 83% and 54%, respectively. Surprisingly, Zn-ICOP, despite having significantly lower CO2 uptake capacity, displayed better catalytic activity than H2-ICOP, owing to a higher number of counter anions (Cl − ) on its surface, which shows the crucial role of the counter anion (Cl − ) in the mechanism of this catalytic reaction.